Biomarkers associated with atherogenesis: current status and promising areas - M. A. Magruk; A. A. Mosikyan; A. Yu. Babenko (Российский кардиологический журнал)
Biomarkers being used as a laboratory test allow diagnosing the disease at an early stage, confirming diagnostic assumptions or evaluating treatment results. The reveal of biomarkers is inextricably linked to an understanding of the pathogenesis of the disease. As a rule, a biomarker is a soluble molecule participating in the pathological process. The reveal of biomarkers of atherogenesis (BMA) is based on hypotheses of the atherosclerosis development. The formation of atherosclerotic plaques is associated with impaired lipid metabolism, inflammation, fibrosis, calcinosis and oxidative stress. Low-density cholesterol is a recognized BMA in terms of the concept of lipid metabolism disorder. Another concept of atherogenesis is inflammatory theory. To date, a large number of molecules that are involved in the inflammatory process in the formation of atherosclerotic plaques have been studied. For most of these molecules, association with cardiovascular diseases has been proven, but they enter clinical practice very slowly. The most widespread among inflammatory biomarkers of atherogenesis is the highly sensitive C-reactive protein. C-reactive protein is not directly associated with the development of atherosclerosis, however, it is formed in response to the inflammatory reaction, therefore it can be used as a BMA. Its main advantages include stability and well-known reference intervals. Other molecules that can directly participate in the formation of atherosclerotic plaques or lead to their instability are also being studied as BMA. To introduce the use of these markers into routine practice, additional studies are needed to establish reference intervals. In recent years, the role of micro RNA as BMA has been increasingly discussed. Micro RNA molecules have a high stability and indirectly reflect the level of expression of genes involved in the development of atherosclerosis. The determination of BMA directly involved in the formation of plaques will contribute to a more accurate diagnosis and assessment of existing and potential therapy for atherosclerosis.